Improving Innovation in Front Line Staff through Lean Management Techniques: A Critical Review - Ridley, Abigail (2012)
Due to an ageing population and the current economic climate the government is looking to improve efficiency in the NHS by doing more with less. Research suggests that the most efficiency gains are to be had by listening to ideas from those at the front line of the organisation. In recent years, lean management has been adopted into health care and shows characteristics that lends itself towards encouraging innovation in health care. The implementation of lean in health care was examined and issues and barriers identified in the context of the NHS as an organisation. Levels of innovation within in the NHS were also identified along with barriers to innovation. The ability of lean management techniques to encourage innovation within front line staff was then discussed, concluding that whilst lean does have many properties that should aid innovation, it will not happen without a wider, cross-organisational implementation across the NHS.